Prevalence and risk factors for Barrett’s esophagus in Taiwan - Chen, Yan-Hua (World J Gastroenterol, 2019)
BACKGROUND: Barrett’s esophagus (BE) is a pre-malignant condition associated with the development of esophageal adenocarcinoma. The prevalence of BE in the general populations of Asian countries ranges from 0.06% to 1%. However, with lifestyle changes in Asian countries and adoption of western customs, the prevalence of BE might have increased. AIM: To determine the current prevalence of BE in Taiwan, and to investigate risk factors predicting the presence of BE. METHODS: This retrospective study was conducted at the Health Evaluation Center of Kaohsiung Veterans General Hospital in Taiwan. Between January 2015 and December 2015, 3385 subjects undergoing routine esophagogastroduodenoscopy examinations as part of a health check-up at the Health Evaluation Center were included. Patient characteristics and endoscopic findings were carefully reviewed. Lesions with endoscopic findings consistent with BE awaiting histological evaluation were judged as endoscopically suspected esophageal metaplasia (ESEM). BE was defined based on extension of the columnar epithelium ≥ 1 cm above the gastroesophageal junction and was confirmed based on the presence of specialized intestinal metaplasia (IM) in the metaplastic esophageal epithelium. Clinical factors of subjects with BE and subjects without BE were compared, and the risk factors predicting BE were analyzed. RESULTS: A total of 3385 subjects (mean age, 51.29 ± 11.42 years; 57.1% male) were included in the study, and 89 among them were confirmed to have IM and presence of goblet cells via biopsy examination. The majority of these individuals were classified as short segment BE (n = 85). The overall prevalence of BE was 2.6%. Multivariate analysis disclosed that old age [odds ratio (OR) = 1.033; 95% confidence interval (CI): 1.012-1.055; P = 0.002], male gender (OR = 2.106; 95%CI: 1.145-3.872; P = 0.017), ingestion of tea (OR = 1.695; 95%CI: 1.043-2.754; P = 0.033), and presence of hiatal hernia (OR = 3.037; 95%CI: 1.765-5.225; P < 0.001) were significant risk factors predicting BE. The independent risk factor for the presence of IM in ESEM lesions was old age alone (OR = 1.029; 95%CI: 1.006-1.053; P = 0.014). CONCLUSION: Current prevalence of BE among the general population in Taiwan is 2.6%. Old age, male gender, ingestion of tea and hiatal hernia are significant risk factors for BE.